Effect of temperature, moisture content and inoculum size on protein increment in Salak seed media (Zalafeed™) - Khairul Farihan, Kasim; Alina Rahayu, Mohamed; Ku Syahidah, Ku Ismail; Noor Hasyierah, Mohd Salleh; Hafiza, Shukor; Mohamed Zulkali, Mohamed Daud (Universiti Putra Malaysia (UPM) & Institution of Chemical Engineers, Malaysia, 2008)
Organized by Universiti Putra Malaysia (UPM) & Institution of Chemical Engineers, Malaysia, 12th - 14th December 2007 at Universiti Putra Malaysia (UPM) Serdang, Selangor.